Systematic Review of Tissue Expansion: Utilization in Non-breast Applications. Issue 1 (January 2021) - Langdell, Hannah C.; Taskindoust, Mahsa; Levites, Heather A.; Mateas, Catalin; Sergesketter, Amanda R.; Kaplan, Samantha J.; Marcus, Jeffrey R.; Erdmann, Detlev
Abstract : Background: Tissue expansion is a versatile reconstructive technique providing well-vascularized local tissue. The current literature focuses largely on tissue expansion for breast reconstruction and in the context of burn and pediatric skin/soft tissue replacement; however, less traditional applications are also prevalent. The aim of this study was to systematically review the utilization of tissue expansion in such less well-characterized circumstances. Methods: The authors conducted a systematic review of all publications describing non-breast applications of tissue expansion. Variables regarding expander specifications, expansion process, and complications were collected and further analyzed. Results: A total of 565 publications were identified. Of these, 166 publications described tissue expansion for "less traditional" indications, which fell into 5 categories: ear reconstruction, cranioplasty, abdominal wall reconstruction, orthopedic procedures, and genital (penile/scrotal and vaginal/vulva) reconstruction. While lower extremity expansion is known to have high complication rates, tissue expander failure, infection, and exposure rates were in fact highest for penile/scrotal (failure: 18.5%; infection: 15.5%; exposure: 12.5%) and vaginal/vulva (failure: 20.6%; infection: 10.3%; exposure: 6.9%) reconstruction. Conclusions: Tissue expansion enables index operations by providing additional skin before definitive reconstruction. Tissue expanders are a valuable option along the reconstructive ladder because they obviate the need for free tissue transfer. Although tissue expansion comes with inherent risk, aggregate outcome failures of the final reconstruction are similar to published rates of complications without pre-expansion. Thus, although tissue expansion requires a staged approach, it remains a valuable option in facilitating a variety of reconstructive procedures. Abstract : Supplemental Digital Content is available in the text.